Bridging Modern Authentication: A Unified Framework for Phishing-Resistant, Usable, and Scalable Enterprise Identity - Dr. Arvind S. Mehta (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
This article presents a comprehensive, theory-driven, and practice-oriented analysis of contemporary web authentication schemes with the explicit aim of proposing an integrated framework that reconciles competing goals of security, phishing resistance, organisational usability, and enterprise scalability. Drawing strictly from the provided literature — spanning foundational cryptography, comparative evaluations of authentication schemes, empirical analyses of credential-related incidents, standards for authorization, modern second-factor mechanisms, and practical incident-cost estimations — the study synthesises prior work to form an explanatory architecture and evidence-based recommendations. The abstracted framework emphasises layered defenses combining public-key cryptography, phishing-resistant multi-factor approaches, behavioural and organisational controls that address compliance costs, and pragmatic deployment patterns guided by standards such as OAuth 2.0 and FIDO2-inspired paradigms. The core contributions are (1) a conceptual model that maps attack surfaces to mitigation families grounded in canonical cryptographic principles (Diffie & Hellman, 1976) and subsequent protocol work; (2) an expanded taxonomy of usability-security tradeoffs informed by empirical usability studies and compliance-budget literature (Brooke, 1995; Beautement et al., 2008; Ciolino et al., 2019); and (3) a decision framework for enterprises to prioritise interventions based on breach cost data and incident vectors (IBM, 2024; Verizon, 2024; Thomas et al., 2017). The article concludes with detailed operational recommendations, limitations of current approaches, and directions for future research that balance rigorous security with real-world constraints on adoption and human behaviour. The paper is intended to serve researchers, security architects, and policy makers seeking a consolidated, evidence-based route to transition modern enterprises toward phishing-resistant and scalable identity assurance. (Maximum 400 words). (Bonneau, 2012; Diffie & Hellman, 1976; IBM, 2024; Lang et al., 2016).